The role of short- and long-duration energy storage in reducing the cost of firm photovoltaic generation - Yang, Guoming; Yang, Dazhi; Liu, Bai; Zhang, Hao (Applied energy, 2024)
Recent literature has confirmed the benefits of jointly optimizing and allocating various firm power enablers, such as photovoltaic (PV) overbuilding & proactive curtailment, geographical smoothing, or energy storage. These enablers facilitate the transformation of variable PV power into effectively dispatchable power, thereby firming up PV generation. However, many previous studies on firm PV generation only considered batteries as the energy storage option, which notoriously elevates the overall system costs owing to the short-duration nature of battery storage. Besides, the implications of the anticipated yet uncertain decrease in storage costs on the economic viability of firm PV and system component sizes remain unclear. This work, therefore, introduces hydrogen as a long-duration (e.g., seasonal) storage option and elucidates the differences between short- and long-duration storage in reducing the cost of firm PV power. Specifically, two facets separate this work from its antecedents: (1) A mixed-integer linear programming model that minimizes the firm kWh premium of the PV–battery–hydrogen system, which possesses the role of both short- and long-duration storage, is proposed to determine the optimal system configuration; (2) the impact of changes in storage options and costs on the energy component ratings is investigated, and the scaling of system economics with these changes is assessed. The analysis reveals that the obtained firm kWh premium stands at 5.42 when the firm 100% PV-supplied system is utilized to fulfill the load demand with an average daily value of 22.04 MWh, while the installation of a 44.81-MWh battery, a 684-kW electrolyzer, and a 540-kW fuel cell, is required to achieve the optimal system costs. Additionally, compared to the future cost change in long-duration storage due to technology updates, the premium is more sensitive to an equal amount of change in the cost of short-duration storage. The results can offer policymakers actionable insights regarding the capacity optimization of PV plants, the strategic deployment of hydrogen systems, and the cost-effective construction of zero-carbon energy networks. [Display omitted] •A model is proposed to optimize the cost of firm PV generation.•The battery, a short-duration storage option, is mainly employed for diurnal storage.•The hydrogen system (long-duration storage) primarily caters to inter-seasonal storage.•The incorporation of long-duration storage lowers the system premium by 10%.•Battery cost reduction diminishes the system cost more than the hydrogen system.